The Effect of Taxation on Immunization Rules and Duration Estimation - HESSEL, CHRISTOPHER A.; HUFFMAN, LUCY (Journal of Finance, 1981)
ABSTRACT Investments in default‐free bonds can be insulated from financial loss due to interest rate changes (via additive shock) by a process known as immunization. The literature on this process ignores taxes. This manuscript focuses on three issues. The first is the development of the tax‐adjusted immunization process with a comparison to the existing literature. The second issue is the microeconomic effect of a shift in only the individual's tax rates on immunization and investment behavior. The third issue is the macroeconomic effect of an across‐the‐board shift in tax rates on immunization and investment behavior.